Investigating the relationship between physical properties of a football and player perceptions - Thompsett, B.; Harland, A.; Roberts, J. (Procedia Engineering, 2016)
Football being one of the most popular sports globally sees the emergence of new ball products and technologies on a regular basis, with the governing body FIFA having set a standard to ensure consistency between products. Despite this, differences are commonly perceived between footballs. The aim of this study was to evaluate players' perceptions in relation to direct and objective measurements of footballs. A paired comparison method was used to evaluate players' perceptions of hardness and weight during passing and shooting exercises of three individual FIFA Approved footballs. Direct measurements of mass and Shore A hardness were obtained as well as quasi-static stiffness values and diameter normal compression ratios during kicking robot impacts. Players perceived with significance, differences between the footballs in respect to hardness for the passing exercise. No initial trends were seen between perceptions of hardness and weight and direct measurements of hardness and mass. An emerging trend between perceptions of hardness and weight and objective measurements of quasi-static stiffness and high-speed impact diameter normal compression ratio was seen suggesting players' perceptions of hardness and weight are more complicated than purely direct measurements of mass and hardness.